ARNTL, CLOCK and PER3 polymorphisms – links with chronotype and affective dimensions. (14th September 2017) - Jankowski, Konrad S.; Dmitrzak-Weglarz, Monika
ABSTRACT: Recently, seven single nucleotide polymorphisms (SNPs) of ARNTL, TIM and PER3 genes were found associated with affective temperaments in bipolar disorder patients. This study aimed to test whether a) the same associations appear in a non-clinical sample; b) the SNPs are related to other affective dimensions; c) the SNPs underpin the associations between chronotype and affective temperaments/dimensions. Three hundred thirty-eight university students completed the Temperament Scale of Memphis, Pisa, Paris and San Diego Auto-questionnaire, the Centre for Epidemiological Studies Depression Scale, the Perceived Stress Scale, the General Health Questionnaire, the Seasonal Pattern Assessment Questionnaire and the Composite Scale of Morningness. Seven SNPs of the ARNTL, TIM and PER3 genes were genotyped. According to nominal significance, ARNTL rs7107287 was associated with a cyclothymic temperament, depressive and stress symptoms, general mental health and perceived negative impact of seasonality, while TIM rs10876890 was associated with a hyperthymic temperament, and the TIM rs2291738 was associated with chronotype. Different SNPs were related to chronotype and affective temperaments/dimensions, and therefore, they seem to not underpin relationships between chronotype and affective dysfunction, that is, in the present study, eveningness was related to dysthymic, cyclothymic and irritable temperaments, more symptoms of depression, stress, worse mental health and a negative impact of seasonality, while morningness was related to hyperthymic temperament. The SNPs associations need further replication given that they did not achieve Bonferroni criteria of significance accounting for the number of polymorphisms considered and tests conducted.